Extracts from The Cochrane Library: antihistamines and/or decongestants for otitis media with effusion (OME) in children. - Burton, M; Rosenfeld, R (2007)
The "Cochrane Corner" is a quarterly section in the Journal that highlights systematic reviews relevant to otolaryngology-head and neck surgery, with invited commentary to highlight implications for clinical decision making. This installment features a Cochrane Review entitled "Antihistamines and/or decongestants for otitis media with effusion (OME) in children," which recommends against treatment because of no demonstrable benefits but significant potential for harm.